Incorporating risk management as part of shariah governance framework in Islamic institution / Mohammad Mahyuddin Khalid … [et al.] - Khalid, Mohammad Mahyuddin; Yaakob, Mohd Ashrof Zaki; Mohd Sirajuddin, Mohd Dasuqkhi; Mahfot, Mahbob (Research Innovation Business Unit, 2014)
Globally, there has been significant interest in literature on risk analysis and management in the past decade or so. However, all these developments revolved around the banking and financial institution, due to extensive research, development and innovation of its institutions and services. While number of Islamic institution like zakat (tithe) and waqf (endowment) has grown substantively in the last few years, research and studies of its risk character and profile are still low. Effective management of risk is fundamental key to any institution’s governance framework. As for Islamic institutions, risk appears to be in many different profiles; financial, personnel, program and others due to interaction with economic, political and social environments. Islamic institutions are faced with this unique risk as a result of special characteristics of the operational structures of the institutions such as operational risk, legal risk and shariah non-compliance risk. This study aims to conduct risk assessment to identify and analyse potential risk in the Islamic institutions with the main objectives to identify, manage and monitor type of risk in zakat and waqf institutions. Although potential risk is difficult to be identified, Islamic institutions must explore ways to manage the potential risk as it might significantly damage their reputation and creditability.